Recommendations of the Global Multiple System Atrophy Research Roadmap Meeting. (9th January 2018) - Walsh, Ryan R.; Krismer, Florian; Galpern, Wendy R.; Wenning, Gregor K.; Low, Phillip A.; Halliday, Glenda; Koroshetz, Walter J.; Holton, Janice; Quinn, Niall P.; Rascol, Olivier; Shaw, Leslie M.; Eidelberg, David; et al.
Abstract : Multiple system atrophy (MSA) is a rare neurodegenerative disorder with substantial knowledge gaps despite recent gains in basic and clinical research. In order to make further advances, concerted international collaboration is vital. In 2014, an international meeting involving leaders in the field and MSA advocacy groups was convened in Las Vegas, Nevada, to identify critical research areas where consensus and progress was needed to improve understanding, diagnosis, and treatment of the disease. Eight topic areas were defined: pathogenesis, preclinical modeling, target identification, endophenotyping, clinical measures, imaging biomarkers, nonimaging biomarkers, treatments/trial designs, and patient advocacy. For each topic area, an expert served as a working group chair and each working group developed priority-ranked research recommendations with associated timelines and pathways to reach the intended goals. In this report, each groups' recommendations are provided.